Strategi Manajemen Berbasis Psikologi untuk Meningkatkan Motivasi Belajar Siswa - Sintia Rosyidah; Olyvia Zalianti; Ryzma Halyza Zuhro; Hilda Zaukia; Mu’alimin Mu’alimin (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Low student learning motivation is one of the main obstacles that affect the smoothness and success of the learning process. To overcome this, a classroom management strategy is needed that not only focuses on technical management, but also considers the psychological aspects of students. This paper reviews the application of management strategies based on psychological principles in order to improve student learning motivation. Through this approach, teachers are expected to be able to recognize differences in student characteristics, help them manage their emotions, and create a positive and supportive learning atmosphere. The strategies discussed include individual understanding, providing appropriate learning encouragement, improving learning skills, managing emotions, and constructive assessments. The results of the discussion show that psychology-based management strategies are able to foster intrinsic learning motivation, increase student involvement in the classroom, and create a conducive learning climate. Thus, this approach can be used as an alternative solution in efforts to improve the quality of education.